Pathophysiological Role of Transient Receptor Potential Mucolipin Channel 1 in Calcium-Mediated Stress-Induced Neurodegenerative Diseases - Santoni, Giorgio; Maggi, Federica; Amantini, Consuelo; Marinelli, Oliviero; Nabissi, Massimo; Morelli, Maria Beatrice (Frontiers in Physiology, 2020)
Mucolipins (TRPML) are endosome/lysosome Ca2+ permeable channels belonging to the family of transient receptor potential channels. In mammals, there are three TRPML proteins, TRPML1, 2, and 3, encoded by MCOLN1-3 genes. Among these channels, TRPML1 is a reactive oxygen species sensor localized on the lysosomal membrane that is able to control intracellular oxidative stress due to the activation of the autophagic process. Moreover, genetic or pharmacological inhibition of the TRPML1 channel stimulates oxidative stress signaling pathways. Experimental data suggest that elevated levels of reactive species play a role in several neurological disorders. There is a need to gain better understanding of the molecular mechanisms behind these neurodegenerative diseases, considering that the main sources of free radicals are mitochondria, that mitochondria/endoplasmic reticulum and lysosomes are coupled, and that growing evidence links neurodegenerative diseases to the gain or loss of function of proteins related to lysosome homeostasis. This review examines the significant roles played by the TRPML1 channel in the alterations of calcium signaling responsible for stress-mediated neurodegenerative disorders and its potential as a new therapeutic target for ameliorating neurodegeneration in our ever-aging population.